Rugonfalvi Kiss István történelem-professzor, a Debreceni m. kir. Tisza István-Tudományegyetem 1932/33. évi Rector Magnificusa - Mudrák, József; Zambon, Csaba (Gerundium, 2018)
Professor of History, István Rugonfalvi Kiss served as Rector Magnificus of the Hungarian Royal István Tisza University of Debrecen in the academic year of 1932-1933. A historian of Székely origin, he first served as the local archivist of the Baron Radvánszky family estate, then he acquired a growing reputation as the chief archivists of Győr County. Starting in 1911, he became college professor of history at the Arts Academy of the Debrecen Protestant College, then from 1914 until his retirement in 1942 he served as professor of Hungarian history of the newly established University of Debrecen. He served as dean several times and he was appointed Rector of the University in the academic year of 1932-1933. In historical scholarship he represented the conservative alternative, thus he was violently opposed to Gyula Szekfű’s view of history. He is the author of work on the last Hungarian uprising of noblemen as well as on the history of the Székely people. After the the Second World War, owing to his previous political activism, he was imprisoned and subsequently he lived in the circle of his family, isolated from professional activity.